Pengaruh Filler Plastik dan Optimasi Faktor Proses Produksi Cellular Lightweight Concrete - Febri Endya, Maharani; Ary Wahyudie, Ilham; Sukanto, Sukanto (Jurnal Inovasi Teknologi Terapan, 2023)
The use of plastic has become a common thing in different lives. The effect of using these plastic products is to create plastic waste. As the population increases, the accumulation of plastic waste will increase. So that it can be done by applying the 3R method, namely reduce, reuse, and recycle. Plastic waste is used as a lightweight brick reinforcement material. This study aimed to determine the factors that most influence the density value of cellular lightweight concrete with plastic filler and optimize the production process. The method used is the Response Surface Methodology (RSM). The experimental design was chosen Central Composite Design with three factors. The independent variables used in this study were the amount of plastic, the fraction of sand: cement, and the volume of water. The amount of plastic used is 2 grams, 3 grams, and 4 grams. The fraction of sand:cement was 4:3, 3.3:2, and 2:1. The volume of water used was 60 mL, 80 mL, and 100 mL. The results of this study indicate that the optimal value for the density of lightweight bricks is found in the amount of plastic of 7.745 grams, the fraction of sand:cement is 5.8:2, and the volume of water is 139.509 mL. The surface response from the second-order equation is the saddle point with the optimal point at the stationary point. The stationary points obtained are 2.821, 2.726, and 1.769. The research analysis results show that the independent variable that most influence the density value is the fraction of sand: cement.